Logistics management optimization in biotechnology: a multi-period model for Isotank transportation - Salinas, Heitor Delivio Sanches; Soares, Lucas de Campos; Tavares, Isadora Prado; Garcia, Mario Vinicio; Leal, Gislaine Camila Lapasini; Lima, Rafael Henrique Palma (Brazilian Journal of Production Engineering, 2025)
Logistics management of isotank transport in a multinational biotechnology company presents significant challenges. The company, with operations in Brazil, uses precision fermentation with genetically modified yeasts to produce specific molecules. The transport of fermented extracts, which requires isotanks, must be optimized to minimize costs and improve the efficiency of the supply chain. This article presents a multiperiod optimization model to address these logistical challenges, using operational research techniques. The proposed model aims to optimize logistical operations and was validated with real data from the company’s operations. The results show improvements in operational costs and supply chain responsiveness. The application of optimization models, adapted to the needs of biotechnology logistics, is highlighted, promoting improvements in logistical performance in similar industrial contexts.